The Influence of Compensation Suitability, Internal Control, Regulatory Enforcement, and the Use of Information Technology on Fraudulent Behaviour in the Management of Village Funds - Oktavia Nindita; Haliah (Jurnal Ekonomi dan Bisnis Digital, 2023)
Preventive measures are needed to prevent fraud in the management of village funds. Fraud prevention measures are a way to reduce opportunities and prevent any activity from evaluating the risk of fraud. The purpose of this study was to determine whether factors such as compnesation suitability, internal control, regulatory enforcement and the use of information technology affect fraudulent behaviour that occurs in the management of village funds. This quantitative research uses the census sampling method and collects data from all village officials in Lambai Sub-district, North Kolaka Regency. In total, 72 village officials agreed to be respondents in this study. The results of this study indicate that the components of compensation suitability and internal control affect fraudulent behaviour negatively and significantly. Meanwhile, regulatory enforcement and the use of information technology affect fraudulent behaviour negatively and insignificantly.